2002
DOI: 10.1002/j.2333-8504.2002.tb01884.x
|View full text |Cite
|
Sign up to set email alerts
|

MINORITY STUDENT SUCCESS: THE ROLE OF TEACHERS IN ADVANCED PLACEMENT PROGRAM® (AP®) COURSES

Abstract: This project described the characteristics and teaching behaviors of those successfully teaching AP® Calculus AB and AP English Literature and Composition to underrepresented minority students. Its purpose was to assist educators in improving the participation and performance of underrepresented minority students in AP classes. Study results showed successful teachers of minority students are good teachers for all groups. They express a high opinion of students, both majority and minority, and hold them to hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…Finally, the College Board study conducted by Burton, Whitman, Yepes-Baraya, Cline, and Kim (2002) contained design elements that were aligned with the purposes of this study. Burton et al focused on determining dispositions and teaching behaviors of school principals, as well as AP Calculus and AP English teachers, with high proportions of underrepresented minority students.…”
Section: Relevant Literaturementioning
confidence: 99%
“…Finally, the College Board study conducted by Burton, Whitman, Yepes-Baraya, Cline, and Kim (2002) contained design elements that were aligned with the purposes of this study. Burton et al focused on determining dispositions and teaching behaviors of school principals, as well as AP Calculus and AP English teachers, with high proportions of underrepresented minority students.…”
Section: Relevant Literaturementioning
confidence: 99%
“…In an analysis of the role of teachers in minority students' successes in the advanced placement (AP) program, Nancy C. Burton and colleagues (2002) found that professional development activities for AP teachers provided participants with the skills necessary to develop the higher-order thinking skills necessary for AP success (students receiving a "3" or better on AP exams). Additionally, AP teachers serve as academic resources for college information for minority students and their parents, and they often use personal experiences to alleviate the concerns of parents of first generation, nontraditional college students (Burton et al 2002).…”
Section: Theory Of Professional Developmentmentioning
confidence: 99%
“…The research also validated the role of teachers as mentors and role models for students, who may have a marginal understanding of geography and geographic careers (Tinto 1975(Tinto , 1988LeVasseur 1993;Burton et al 2002;Foster and Boehm 2002;Adeyemi 2009;Foster 2009). By understanding the long-term effects of content specific professional development on participating teachers, the discipline may better recruit and retain high-achieving minority students.…”
mentioning
confidence: 96%
“…AP course programs are not spreading equally across the nation as troubling ethnic and socioeconomic gaps remain. A College Board study found that only 33% of the expected frequency of enrollment for African Americans and Hispanics were taking AP courses (Burton, Whitman, Yepes-Baraya, Cline, & Kim, 2002). This study reported low proportions from AP teachers who are from ethnic minority backgrounds.…”
mentioning
confidence: 96%